2020
DOI: 10.1111/pce.13867
|View full text |Cite
|
Sign up to set email alerts
|

SlTLFP8 reduces water loss to improve water‐use efficiency by modulating cell size and stomatal density via endoreduplication

Abstract: Improving plant water-use efficiency (WUE) is important to plant survival and crop yield in the context of water limitation. In this study, SlTLFP8 (Tubby-like F-box protein 8) was identified as an osmotic-induced gene in tomato. Transgenic tomato with up-regulated expression of SlTLFP8 showed enhanced water-deficient resistance, whereas knockout mutants generated by CRISPR/Cas9 were more sensitive to water deficit. SlTLFP8 overexpression significantly enhanced WUE by suppressing transpiration under both water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 59 publications
2
41
1
Order By: Relevance
“…Zhang et al explored the expression of SlTLPs in tomato fruit founded that SlTLP1, SlTLP2, SlTLP4 and SlTLP5 are ripening-related, and SlTLP1 and SlTLP2 may play a role in ethylene-dependent fruit ripening [30]. Our previous works imply that SlTLFP8 regulated stomatal density through nuclear endoreduplication and affected water-deficient resistance and water-use efficiency [31].…”
Section: Introductionmentioning
confidence: 84%
“…Zhang et al explored the expression of SlTLPs in tomato fruit founded that SlTLP1, SlTLP2, SlTLP4 and SlTLP5 are ripening-related, and SlTLP1 and SlTLP2 may play a role in ethylene-dependent fruit ripening [30]. Our previous works imply that SlTLFP8 regulated stomatal density through nuclear endoreduplication and affected water-deficient resistance and water-use efficiency [31].…”
Section: Introductionmentioning
confidence: 84%
“…Considering that ERD1 could be activated by ANAC019/ANAC072 in Arabidopsis [32], and the expression of ERD1 was prominently upregulated in PwNAC11 OE lines, we subsequently conducted the yeast one-hybrid (Y1H) assays to confirm the regulation of PwNAC11 on ERD1 promoter region. In contrast with the negative control, both pGADT7-PwNAC11 + pAbAi-ERD1pro and pGADT7-ABF3 + pAbAi-ERD1pro yeast strains could grow on SD/Ura-Leu + AbA selective medium (Figure S3), suggesting both Recent studies indicated that increased ABA content could promote stomatal closure to improve the drought tolerance of plants [31]. We further observed and calculated the level of close stomata by exogenously applying ABA in different lines.…”
Section: Pwnac11 and Abf3 Combine With The Promoter Region Of Erd1mentioning
confidence: 91%
“…Endoreduplication has an important role in modulating plant organ or tissue size ( Peng et al, 2015 ; Li et al, 2020 ). Most studies on this topic have indicated that cyclin proteins are downstream target genes involved in organ size ( Breuer et al, 2009 , 2012 ).…”
Section: Phytohormones Are Important Regulators Of Trichome Developmentmentioning
confidence: 99%
“…It is therefore very important to reveal how genes reach the right state at the right place and at the right time. Although many RNA-seq techniques have been used to study the development of glandular trichomes (Li et al, 2020;Liao et al, 2020), progress in understanding glandular trichome development has been very slow. Since many glandular trichomes are multicellular, the function of each cell is different, resulting in different levels of mRNA in each cell.…”
Section: Single-cell Rna Sequencing Reveals Spatiotemporal Trichome Developmentmentioning
confidence: 99%